Graphene Oxide: An Efficient Material and Recent Approach for Biotechnological and Biomedical Applications - Singh, D (Elsevier Ltd, 2018)
The two-dimensional (2D) derivative of graphite termed graphene has widespread applications in various frontiers areas of nanoscience and nanotechnologies. Graphene in its oxidized form named as graphene oxide (GO) has a mixed structure equipped with various oxygen containing functional groups (epoxy, hydroxyl, carboxylic and carbonyl etc.) provides attachment sites to various biological molecules including protein, deoxyribonucleic acid (DNA), ribonucleic acid (RNA) etc. The attached biological molecules with the help of functional groups make it a promising candidate in research field of biotechnological and biomedical applications. The ease of processability and functionalization in aqueous solution due to available functional groups, amphiphilicity, better surface enhanced Raman scattering (SERS), fluorescence and its quenching ability better than graphene make GO a promising candidate for various biological applications. The amphipathetic nature and high surface area of the GO not only prepare it as a biocompatible, soft and flexible intra/inter cellular carrier but also provides long-term biocompatibility with very low cytotoxicity. Inspite of this, still we lack a very recent review for advanced biological applications of graphene oxide. This review deals the bio application of GO and the recent advancement as a biosensors, antibacterial agent, early detection of cancer, cancer cell imaging/mapping, targeted drug delivery and gene therapy etc. © 2018 Elsevier B.V.